Factors Affecting the Environmental Quality Index in Regencies Municipalities in Jambi Province - Muhammad Bayu Saputra; M Ridwansyah; Parmadi Parmadi (Jurnal Ekonomika dan Manajemen, 2026)
This study is motivated by the need to assess environmental quality amid economic development in Jambi Province. It examines the influence of socio-economic factors and environmental quality on the Environmental Quality Index (EQI) across regencies/municipalities in the province. Using a quantitative approach and panel data regression with secondary data from the Central Statistics Agency, the results show that unemployment rate, as well as the Air Quality Index, Water Quality Index, and Land Quality Index, have a significant effect on the Environmental Quality Index. In contrast, the poverty rate and Gross Regional Domestic Product (GRDP) per capita do not have a significant effect. In conclusion, synergy between economic growth and environmental conservation is necessary to improve the Environmental Quality Index in Jambi. These findings are expected to provide input for policymakers in balancing development strategies with environmental sustainability.